Perbandingan Strategi Competitive Analysis Antara PT Gudang Garam Dan HM Sampoerna Menggunakan Metode Analisis Porter’s Five Forces - Nicola Firmani; Alberto Yosef; Valencia Cicilia; Filippo Defitra (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to compare the competitive analysis strategies of PT Gudang Garam and HM Sampoerna using Porter's Five Forces analysis method. Porter's Five Forces is a framework for analyzing an industry and understanding its competitive attractiveness and strengths. This study collected secondary data consisting of financial statements, annual reports, industry publications and other relevant sources. This information is used to analyze Porter's five forces, namely the threat of competitors, the threat of substitute products or services, the bargaining power of supplier power, the bargaining power of purchasing power, and the threat of new competitors entering the market. The results of the analysis show that the two companies, PT Gudang Garam and HM Sampoerna operate in a highly competitive industry. As for the threat of competitors, both companies face intense competition in the cigarette market. They compete with each other in the areas of product innovation, marketing and market access. Regarding supplier bargaining power, both companies depend on raw materials such as tobacco. Negotiating purchasing power is also an important factor in this area. Consumers have significant bargaining power when choosing cigarette brands. The threat of new competitors is also significant, but the heavy regulation of the Indonesian cigarette industry presents barriers for new competitors to enter the market.In general, both companies must constantly monitor the industry environment and adapt to changes that occur. You must develop a strategy